Tinjauan Pelaksanaan General Consent pada Pasien Baru Rawat Jalan RSUP dr. Sardjito - Bhre Diansyah; Gamasiano Alfiansyah; Sustin Farlinda (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2020)
One of the accreditation instruments is Patient and Family Rights (HPK) 6.3 which states that patients andtheir families were provided with an explanation of the scope of the general consent. Based on preliminaryresearch at the outpatient registration unit at RSUP dr. Sardjito Yogyakarta, the average new registeredpatients reached 43.25 patients per day and 89% of them did not receive an explanation about thecontents of the general consent form. This research aims to identify the current general consent form foroutpatients in 2020, identify the procedure applied in delivering information of the general consent foroutpatients, and identify factors obstructing the application of the general consent. This research wasqualitative. The data were collected through interviews and observations. The subjects of the researchinvolved officers of the inpatient registration unit at RSUP dr. Sardjito Yogyakarta and the head of themedical record and health information department. The results of this research show that the registrationofficers do not inform the general consent information for new patients because they have more concernon the speed of registration process without telling the content of general consent and unavailability ofSOP in providing general consent information that cause less proper work implementation.